Chemistry and Cosmetics - Aguirre, J. Dafhne (2022)
At first glance it may seem strange to connect chemistry with cosmetics. Nothing further from the truth since both are a constant in our daily lives. The average person uses at least 5 cosmetic products daily, which translates into at least 150 different chemical compounds being applied into our bodies every day. Unfortunately, an increase in misinformation has led to an ever-growing fear of chemical compounds.  Consequences of the misrepresentation of chemicals, good and bad, have plagued the cosmetics industry. One of the most affected compounds by misinformation are parabens, which are commonly used as preservatives in cosmetic products. The consensus of both scientific and dermatological community is that parabens are not only risk-free, but also highly beneficial to stop contamination with fungi and other microorganisms. Currently, parabens are considered some of the least allergenic preservatives available, with rates of contact sensitization between 0.5% to 1.4%. Nevertheless, consumers and clean beauty movement supporters have it classified as a high-risk product that should be completely banned. On one hand, by not using parabens, products risk being contaminated, on the other hand laboratories are now trying to find other alternatives to these compounds. Being well informed about the ingredients of a product is the consumers’ right of, and an obligation of the industry, but it does not relieve the public to its responsibility to be well-informed. At the same time, the responsibility of the scientific community is to try to inform the public using simpler terms and making science accessible to everyone.